(untitled) (Journal of Shaheed Suhrawardy Medical College, 2012)
Adult rhabdomyosarcoma in the head & neck is extremely rare & carries a poor prognosis. They should be considered as a distinct clinical entity. The authors report a case of embryonal rhabdomyosarcoma in an adult female in Hypopharynx treated with chemo-radiotherapy & surgical excision., The patient responded to treatment & 7 yrs later she is still alive with no signs of metastatic disease. DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12171 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.22-24